A review of methods to track oil in Arctic waters - St. Martin, Joseph W.; United States. Coast Guard. Office of Research and Development.; U.S. Coast Guard Research & Development Center. (Washington, D.C. : U.S. Department of Transportation, U.S. Coast Guard, Office of Research and Development, 1985)
"June 1985." Cover title. Bibliography: p. 19. Final report. Mode of access: Internet.